Autoantibodies in COVID-19 survivors with post-COVID symptoms: a systematic review - Notarte, Kin Israel; Carandang, Timothy Hudson David Culasino; Velasco, Jacqueline Veronica; Pastrana, Adriel; Ver, Abbygail Therese; Manalo, Gerald Neil; Ng, Jeremy Ace; Grecia, Steven; Lippi, Giuseppe; Henry, Brandon Michael; Fernández-de-las-Peñas, César (Frontiers in Immunology, 2024)
Objective The long-lasting persistence of autoantibodies stands as one of the hypotheses explaining the multisystemic manifestations seen in individuals with post-COVID-19 condition. The current review offers restricted insights into the persistence of autoantibodies in plasma/serum in people with post-COVID symptoms. Methods PubMed/MEDLINE, CINAHL, EMBASE, and Web of Science databases, as well as on medRxiv and bioRxiv preprint servers were searched up to January 5th, 2024. Papers investigating the presence of autoantibodies in plasma/serum samples in people with post-COVID symptoms were included. The Newcastle-Ottawa Scale (NOS) was used to assess methodological quality. Results From 162 identified records, five articles met all inclusion criteria; four studies included infected controls with no post-COVID symptoms whereas all five studies included non-infected controls (410 COVID-19 survivors with post-COVID symptoms, 223 COVID-19 survivors with no post-COVID symptoms as controls and 266 non-infected healthy controls). Four studies concluded that the presence of autoantibodies had a potential (but small) role in post-COVID-19 condition whereas one study concluded that autoantibodies were not associated. Quality assessment showed all studies had high methodological quality. Conclusion Although evidence suggests that persistent autoantibodies can be associated with post-COVID symptoms, the clinical relevance of their presence seems modest at this stage. Current results highlight further research to clarify the role of autoantibodies in the development of post-COVID symptoms, guiding the development of tailored diagnostic and treatment approaches to enhance patient outcomes. Systematic review registration https://osf.io/vqz28.